Influence of a groove-structured vortex generator on the drag reduction characteristics of a multiphase pump - Han, Wei; Yang, Xiang; Zhang, Jing; Xiao, Mingzhen; Yan, Lumin; Zhou, Juping; Gu, Zhenye; Yang, Shiqi (Frontiers in Energy Research, 2023)
The oil-gas mixture pump significantly contributes to marginal oil field extraction and remote transportation of deep-sea oil. Nevertheless, during the operation of the mixture pump, it is inevitable to encounter problems like the separation of the mixed media from the hydraulic components as well as the gas phase from the liquid phase, which leads to enhancing the flow resistance of the mixed media. Therefore, this study investigates the influence of groove-structure vortex generator on the drag reduction characteristics of helical axial-flow gas-liquid multiphase pump under the design flow rate condition and various inlet gas content rates. The findings show that the vortex generator with diverse groove depths can prevent the separation of the mixed media from the blade suction surface effectively and minimize the flow resistance of the media in the 1/10 of the blade inlet. In particular, excellent drag reduction results were gained with a maximum drag reduction rate of 36.7% when the relative depth was 3/40. In addition, the efficiency of the mixture pump increased by a maximum of 2.1%, and the head increased by a maximum of 4.3%. The significance of this study lies in its potential to further optimize the design and performance of gas-liquid multiphase pumps. It provides new insights into the design and application of vortex generators. It offers robust support for the optimization and enhancement of gas-liquid multiphase pump.